Antarctica's Gamburtsev Province (AGAP) Project - Radio-echo sounding data (2007-2009) ... - Corr, Hugh; Ferraccioli, Fausto; Jordan, Tom; Robinson, Carl (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
Radio-echo sounding data was collected using 150 MHz ice-penetrating radars with bandwidths of 15-20 MHz. This data was collected as part of the seven nation Antarctica's Gamburtsev Province (AGAP) expedition during the International Polar Year 2007-2009, and used to acquire a detailed image of the ice sheet bed deep in the interior of East Antarctica. Airborne geophysical methods were used to understand the fundamental structure shrouded beneath Dome A. Two twin Otter aircraft - one BAS, one United States Antarctic Program (USAP) - equipped with ice-sounding radars, laser ranging systems, gravity meters and magnetomemeters, operated from camps located on either side of Dome A. ... : Radar data and details on survey location and design are presented in Rose et al. (2013). Radar data collection by BAS used the PASIN radar echo sounding system (table 1 (Corr et al., 2007)). USAP data was collected using a 150-MHz system with bandwidths of 15 to 20 MHz (Bell et al, 2011). Data provided here includes picks of surface and ice sheet bed elevation. BAS flights include turns and transit flights, whereas USAP data is confined to line portions only. Small (a few minutes) time jumps are contained in a limited number of survey lines as a result of the re-booting of the PASIN system. Note in the database split by line the sections are defined as follows L= main survey grid lines, T=main survey tie lines, P=long transits, D=turns. Channel description: Basic Channels Date UTC date (YYYY/MM/DD) Time UTC time (HH:MM:SS.SS) FlightID Sequential flight number and survey ID e.g. W12 Line_name Line Number e.g. LW200.1 Lon Longitude WGS 1984 (note: longitudes go from 0 to 360 degrees) Lat Latitude WGS 1984 x x ...